Anti-inflammatory Nanoparticle for Prevention of Atherosclerotic Vascular Diseases - Koga, Jun-ichiro (J Atheroscler Thromb, 2016)
Recent technical innovation has enabled chemical modifications of small materials and various kinds of nanoparticles have been created. In clinical settings, nanoparticle-mediated drug delivery systems have been used in the field of cancer care to deliver therapeutic agents specifically to cancer tissues and to enhance the efficacy of drugs by gradually releasing their contents. In addition, nanotechnology has enabled the visualization of various molecular processes by targeting proteinases or inflammation. Nanoparticles that consist of poly (lactic-co-glycolic) acid (PLGA) deliver therapeutic agents to monocytes/macrophages and function as anti-inflammatory nanoparticles in combination with statins, angiotensin receptor antagonists, or agonists of peroxisome proliferator-activated receptor-γ (PPARγ). PLGA nanoparticle-mediated delivery of pitavastatin has been shown to prevent inflammation and ameliorated features associated with plaque ruptures in hyperlipidemic mice. PLGA nanoparticles were also delivered to tissues with increased vascular permeability and nanoparticles incorporating pitavastatin, injected intramuscularly, were retained in ischemic tissues and induced therapeutic arteriogenesis. This resulted in attenuation of hind limb ischemia. Ex vivo treatment of vein grafts with imatinib nanoparticles before graft implantation has been demonstrated to inhibit lesion development. These results suggest that nanoparticle-mediated drug delivery system can be a promising strategy as a next generation therapy for atherosclerotic vascular diseases.